Childhood-onset hereditary spastic paraplegia and its treatable mimics - Ebrahimi-Fakhari, Darius; Saffari, Afshin; Pearl, Phillip L. (Molecular genetics and metabolism, 2022)
Early-onset forms of hereditary spastic paraplegia and inborn errors of metabolism that present with spastic diplegia are among the most common “mimics” of cerebral palsy. Early detection of these heterogenous genetic disorders can inform genetic counseling, anticipatory guidance, and improve outcomes, particularly where specific treatments exist. The diagnosis relies on clinical pattern recognition, biochemical testing, neuroimaging, and increasingly next-generation sequencing-based molecular testing. In this short review, we summarize the clinical and molecular understanding of: 1) childhood-onset and complex forms of hereditary spastic paraplegia (SPG5, SPG7, SPG11, SPG15, SPG35, SPG47, SPG48, SPG50, SPG51, SPG52) and, 2) the most common inborn errors of metabolism that present with phenotypes that resemble hereditary spastic paraplegia.
Online verfügbar 24 Juni 2021, Artikelversion 8 Dezember 2022
Gesehen am 20.01.2023